Mosquito Research Recent Advances in Pathogen Interactions, Immunity, and Vector Control Strategies - Puerta-Guardo, Henry; Manrique-Saide, Pablo (IntechOpen, 2023)
With around 3,500 species identified so far, mosquitoes can be found in virtually every environment and continent around the globe. Blood-feeding biters (e.g., Anopheles, Culex, Aedes, Ochlerotatus, and Mansonia) are among the most influential vectors for harboring and transmitting mosquito-borne diseases (MBDs) such as Zika, Japanese encephalitis, West Nile fever, dengue fever, yellow fever, and malaria, among other diseases. More than 700 million human infections and 725,000 deaths occur every year. Mosquitoes are increasing in number worldwide, yet there are still no effective vaccines or prevention strategies. Thus, traditional vector control strategies remain the most common ways to combat these diseases. Despite this, MBDs linger as one of the major challenges for public health and vector control programs at both global and local levels. This book provides a comprehensive overview of MBDs and vector control strategies.